(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effectiveness of using simulation-based methods in developing problem-solving skills for nursing students in pre-clinical practice courses at Van Hien University (VHU). Methods: A quasi-experimental study was conducted with 51 third- and fourth-year nursing students at VHU. A problem-solving skill assessment questionnaire was administered before and after the simulation method was applied in pre-clinical practice. The average scores before and after the intervention were compared. Results: A total of 51 students participated in the study (35 third-year students and 16 fourth-year students). The average score on the EM PSI scale before the practice was 62.2 ± 11.1. After applying the simulation, the EM PSI score increased to 72.7 ± 9.7. The mean difference was 10.5 points (p < 0.05), indicating a significant improvement in problem-solving skills after the simulation. Specifically, significant improvements were observed in two subscales: “Confidence in problem-solving” (increased by 2.9 points) and “Self-control” (increased by 2.6 points). Conclusion: The results demonstrate that the use of simulation in pre-clinical practice significantly enhances problem-solving skills for nursing students, suggesting that this method should be widely and systematically implemented in nursing education.